Field performance of shrunken-2 super-sweet corn populations derived from tropical field maize × shrunken-2 super-sweet corn crosses in Ibadan, Nigeria (2019)
The conversion of tropical field corn genotypes into sweet corn could broaden the genetic base and improve yield and adaptation of sweet corn varieties. In this study, the performance of shrunken-2 (sh2) super-sweet corn populations derived from crosses between a sh2 population and tropical field corn genotypes were evaluated in Ibadan. experiments were conducted using randomised complete block design with three replicates. Data were collected on agronomic and fresh ear yield traits, and then subjected to analysis of variance. Significant genotypic differences were observed among the populations with most of the derived populations significantly superior to the donor population for most of the traits. Yield of marketable cobs ranged from 5.80 to 7.63 t/ha (mean = 6.84 t/ha). Six derived populations had significantly higher yield of marketable cobs than the donor population. On the average, 83.1% of the number of cobs harvested was marketable. Husk cover scores ranged from 2.8 to 6.8, with all the derived populations having significantly lower husk cover scores than the donor population. The results indicated that the conversion of the field corn genotypes into super-sweet corn was effective in the development of new super-sweet corn populations. The observed genetic differences could be exploited in further breeding programmes.